FeMn with Phases of a Degradable Ag Alloy for Residue-Free and Adapted Bioresorbability - Krüger, Jan Tobias; Hoyer, Kay-Peter; Huang, Jingyuan; Filor, Viviane; Mateus-Vargas, Rafael Hernan; Oltmanns, Hilke; Meißner, Jessica; Grundmeier, Guido; Schaper, Mirko (Journal of Functional Biomaterials)
The development of bioresorbable materials for temporary implantation enables progress in medical technology. Iron (Fe)-based degradable materials are biocompatible and exhibit good mechanical properties, but their degradation rate is low. Aside from alloying with Manganese (Mn), the creation of phases with high electrochemical potential such as silver (Ag) phases to cause the anodic dissolution of FeMn is promising. However, to enable residue-free dissolution, the Ag needs to be modified. This concern is addressed, as FeMn modified with a degradable Ag-Calcium-Lanthanum (AgCaLa) alloy is investigated. The electrochemical properties and the degradation behavior are determined via a static immersion test. The local differences in electrochemical potential increase the degradation rate (low pH values), and the formation of gaps around the Ag phases (neutral pH values) demonstrates the benefit of the strategy. Nevertheless, the formation of corrosion-inhibiting layers avoids an increased degradation rate under a neutral pH value. The complete bioresorption of the material is possible since the phases of the degradable AgCaLa alloy dissolve after the FeMn matrix. Cell viability tests reveal biocompatibility, and the antibacterial activity of the degradation supernatant is observed. Thus, FeMn modified with degradable AgCaLa phases is promising as a bioresorbable material if corrosion-inhibiting layers can be diminished.
Keywords: Biomedical Engineering; Biomaterials

Enhancement of the delamination resistance of adhesive film coated surface laser melted aluminum 7075-T6 alloy by aminophosphonic acid adsorption - Vieth, P.; Garthe, M.-A.; Voswinkel, Dietrich; Schaper, Mirko; Grundmeier, Guido (Surface and Coatings Technology)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Surfaces and Interfaces; Condensed Matter Physics; General Chemistry

Tribo-functional PVD thin films deposited onto additively manufactured Ti6Al7Nb for biomedical applications - Tillmann, Wolfgang; Lopes Dias, Nelson Filipe; Kokalj, David; Stangier, Dominic; Hein, Maxwell; Hoyer, Kay-Peter; Schaper, Mirko; Gödecke, Daria; Oltmanns, Hilke; Meißner, Jessica (Materials Letters)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Characterization and analysis of plastic instability in an ultrafine‐grained medium Mn TRIP steel - Teng, Zhenjie; Wu, Haoran; Pramanik, Sudipta; Hoyer, Kay-Peter; Schaper, Mirko; Zhang, Hanlon; Boller, Christian; Starke, Peter (Advanced Engineering Materials)
Keywords: Condensed Matter Physics; General Materials Science

Modiﬁcation of Iron with Degradable Silver Phases Processed via Laser Beam Melting for Implants with Adapted Degradation Rate - Krüger, Jan Tobias; Hoyer, Kay-Peter; Andreiev, Anatolii; Schaper, Mirko; Zinn, Carolin (Advanced Engineering Materials)

Additively Manufactured Nested and Non-Nested Cellular Solids for Effective Stress Distribution and Thermal Insulation Applications: An Experimental and Finite Element Analysis Study - Pramanik, Sudipta; Milaege, Dennis; Hoyer, Kay-Peter; Schaper, Mirko (Crystals)
In this study, the design, additive manufacturing and experimental as well as simulation investigation of mechanical and thermal properties of cellular solids are addressed. For this, two cellular solids having nested and non-nested structures are designed and additively manufactured via laser powder bed fusion. The primary objective is to design cellular solids which absorb a significant amount of energy upon impact loading without transmitting a high amount of stress into the cellular solids. Therefore, compression testing of the two cellular solids is performed. The nested and non-nested cellular solids show similar energy absorption properties; however, the nested cellular solid transmits a lower amount of stress in the cellular structure compared to the non-nested cellular solid. The experimentally measured strain (by DIC) in the interior region of the nested cellular solid is lower despite a higher value of externally imposed compressive strain. The second objective of this study is to determine the thermal insulation properties of cellular solids. For measuring the thermal insulation properties, the samples are placed on a hot plate; and the surface temperature distribution is measured by an infrared camera. The thermal insulating performance of both cellular types is sufficient for temperatures exceeding 100 °C. However, the thermal insulating performance of a non-nested cellular solid is slightly better than that of the nested cellular solid. Additional thermal simulations predict a relatively higher temperature distribution on the cellular solid surfaces compared to experimental results. The simulated residual stress shows a similar distribution for both types, but the magnitude of residual stress is different for the cellular solids upon cooling from different temperatures of the hot plate.
Keywords: Inorganic Chemistry; Condensed Matter Physics; General Materials Science; General Chemical Engineering

FeMn with Phases of a Degradable Ag Alloy for Residue-Free and Adapted Bioresorbability - Krüger, Jan Tobias; Hoyer, Kay-Peter; Huang, Jingyuan; Filor, Viviane; Mateus-Vargas, Rafael Hernan; Oltmanns, Hilke; Meißner, Jessica; Grundmeier, Guido; Schaper, Mirko (Journal of Functional Biomaterials)
The development of bioresorbable materials for temporary implantation enables progress in medical technology. Iron (Fe)-based degradable materials are biocompatible and exhibit good mechanical properties, but their degradation rate is low. Aside from alloying with Manganese (Mn), the creation of phases with high electrochemical potential such as silver (Ag) phases to cause the anodic dissolution of FeMn is promising. However, to enable residue-free dissolution, the Ag needs to be modified. This concern is addressed, as FeMn modified with a degradable Ag-Calcium-Lanthanum (AgCaLa) alloy is investigated. The electrochemical properties and the degradation behavior are determined via a static immersion test. The local differences in electrochemical potential increase the degradation rate (low pH values), and the formation of gaps around the Ag phases (neutral pH values) demonstrates the benefit of the strategy. Nevertheless, the formation of corrosion-inhibiting layers avoids an increased degradation rate under a neutral pH value. The complete bioresorption of the material is possible since the phases of the degradable AgCaLa alloy dissolve after the FeMn matrix. Cell viability tests reveal biocompatibility, and the antibacterial activity of the degradation supernatant is observed. Thus, FeMn modified with degradable AgCaLa phases is promising as a bioresorbable material if corrosion-inhibiting layers can be diminished.
Keywords: Biomedical Engineering; Biomaterials

LPBF Manufactured Functionally Graded Lattice Structures Obtained by Graded Density and Hybrid Poisson’s Ratio - Abdelaal, Osama; Hengsbach, Florian; Schaper, Mirko; Hoyer, Kay-Peter (Materials)
The additive manufacturing (AM) of innovative lattice structures with unique mechanical properties has received widespread attention due to the capability of AM processes to fabricate freeform and intricate structures. The most common way to characterize the additively manufactured lattice structures is via the uniaxial compression test. However, although there are many applications for which lattice structures are designed for bending (e.g., sandwich panels cores and some medical implants), limited attention has been paid toward investigating the flexural behavior of metallic AM lattice structures with tunable internal architectures. The purpose of this study was to experimentally investigate the flexural behavior of AM Ti-6Al-4V lattice structures with graded density and hybrid Poisson’s ratio (PR). Four configurations of lattice structure beams with positive, negative, hybrid PR, and a novel hybrid PR with graded density were manufactured via the laser powder bed fusion (LPBF) AM process and tested under four-point bending. The manufacturability, microstructure, micro-hardness, and flexural properties of the lattices were evaluated. During the bending tests, different failure mechanisms were observed, which were highly dependent on the type of lattice geometry. The best response in terms of absorbed energy was obtained for the functionally graded hybrid PR (FGHPR) structure. Both the FGHPR and hybrid PR (HPR) structured showed a 78.7% and 62.9% increase in the absorbed energy, respectively, compared to the positive PR (PPR) structure. This highlights the great potential for FGHPR lattices to be used in protective devices, load-bearing medical implants, and energy-absorbing applications.
Keywords: General Materials Science

Determination of the burst pressure of pillow plates using finite element methods - Zibart, Alexander; Spang, Bernhard; Kenig, Eugeny Y. (Computer Aided Chemical Engineering)

On the influence of physical vapor deposited thin coatings on the low-cycle fatigue behavior of additively processed Ti-6Al-7Nb alloy - Hein, Maxwell; Lopes Dias, Nelson Filipe; Kokalj, David; Stangier, Dominic; Hoyer, Kay-Peter; Tillmann, Wolfgang; Schaper, Mirko (International Journal of Fatigue)
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering; Mechanics of Materials; General Materials Science; Modeling and Simulation

Formation of insoluble silver-phases in an iron-manganese matrix for bioresorbable implants using varying laser beam melting strategies - Krüger, Jan Tobias; Hoyer, Kay-Peter; Hengsbach, Florian; Schaper, Mirko (Journal of Materials Research and Technology)
Keywords: Metals and Alloys; Surfaces; Coatings and Films; Biomaterials; Ceramics and Composites

Formation of insoluble silver-phases in an iron-manganese matrix for bioresorbable implants using varying laser beam melting strategies - Krüger, Jan Tobias; Hoyer, Kay-Peter; Hengsbach, Florian; Schaper, Mirko (Journal of Materials Research and Technology)
Keywords: Metals and Alloys; Surfaces; Coatings and Films; Biomaterials; Ceramics and Composites

Additively manufactured novel Ti6Al7Nb circular honeycomb cellular solid for energy absorbing applications - Pramanik, Sudipta; Milaege, Dennis; Hoyer, Kay-Peter; Schaper, Mirko (Materials Science and Engineering: A)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Heat Treatments of Metastable β Titanium Alloy Ti-24Nb-4Zr-8Sn Processed by Laser Powder Bed Fusion - Hein, Maxwell; Lopes Dias, Nelson Filipe; Pramanik, Sudipta; Stangier, Dominic; Hoyer, Kay-Peter; Tillmann, Wolfgang; Schaper, Mirko (Materials)
Titanium alloys, especially β alloys, are favorable as implant materials due to their promising combination of low Young’s modulus, high strength, corrosion resistance, and biocompatibility. In particular, the low Young’s moduli reduce the risk of stress shielding and implant loosening. The processing of Ti-24Nb-4Zr-8Sn through laser powder bed fusion is presented. The specimens were heat-treated, and the microstructure was investigated using X-ray diffraction, scanning electron microscopy, and transmission electron microscopy. The mechanical properties were determined by hardness and tensile tests. The microstructures reveal a mainly β microstructure with α″ formation for high cooling rates and α precipitates after moderate cooling rates or aging. The as-built and α″ phase containing conditions exhibit a hardness around 225 HV5, yield strengths (YS) from 340 to 490 MPa, ultimate tensile strengths (UTS) around 706 MPa, fracture elongations around 20%, and Young’s moduli about 50 GPa. The α precipitates containing conditions reveal a hardness around 297 HV5, YS around 812 MPa, UTS from 871 to 931 MPa, fracture elongations around 12%, and Young’s moduli about 75 GPa. Ti-24Nb-4Zr-8Sn exhibits, depending on the heat treatment, promising properties regarding the material behavior and the opportunity to tailor the mechanical performance as a low modulus, high strength implant material.
Keywords: General Materials Science

Orientation-Dependent Indentation Behaviour of Additively Manufactured FeCo Sample: A Quasi In-Situ Study - Pramanik, Sudipta; Tasche, Frederik; Hoyer, Kay-Peter; Schaper, Mirko (Magnetism)
The quasi in-situ indentation behaviour of <110>||BD and <111>||BD-oriented grains in a FeCo alloy is studied in this investigation. The effect of build height on melt pool shape and melt pool size is also studied by finite element method simulations. As the building height increases, the aspect ratio of the elliptical melt pool increases. Correspondingly, the effect of the laser scan speed on the melt pool shape and size is studied by the finite element method, because, as the laser scan speed increases, the aspect ratio of the elliptical melt pool increases, too. The microstructural characterisation of the indentation area before and after indentation is performed by electron backscatter diffraction (EBSD). Based on the EBSD data grain reference orientation deviation (GROD), calculations are performed to describe the effect of indentations on the neighbouring grain orientations. High GROD angles are detected in the neighbouring grain region adjoining the indented grain. An in-depth slip trace analysis shows the activation of all three slip systems ({110}<111>, {112}<111> and {123}<111>) which is also confirmed by slip lines on the sample surface that are detected by laser scanning confocal microscopy. A high concentration of geometrically necessary dislocations (GNDs) are observed on the adjoining area to the indentation. Local surface topography measurements by laser scanning confocal microscopy confirmed the formation of pile-ups near the indentation.
Keywords: General Earth and Planetary Sciences; General Environmental Science

Tribo-functional PVD thin films deposited onto additively manufactured Ti6Al7Nb for biomedical applications - Tillmann, Wolfgang; Lopes Dias, Nelson Filipe; Kokalj, David; Stangier, Dominic; Hein, Maxwell; Hoyer, Kay-Peter; Schaper, Mirko; Gödecke, Daria; Oltmanns, Hilke; Meißner, Jessica (Materials Letters)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Influence of proteins on the corrosion of a conventional and selective laser beam melted FeMn alloy in physiological electrolytes - Huang, Jingyuan; Orive, Alejandro Gonzalez; Krüger, Jan Tobias; Hoyer, Kay-Peter; Keller, Adrian; Grundmeier, Guido (Corrosion Science)
Keywords: General Materials Science; General Chemical Engineering; General Chemistry

Characterization and Analysis of Plastic Instability in an Ultrafine‐Grained Medium Mn TRIP Steel - Teng, Zhenjie; Wu, Haoran; Pramanik, Sudipta; Hoyer, Kay-Peter; Schaper, Mirko; Zhang, Hanlong; Boller, Christian; Starke, Peter (Advanced Engineering Materials)
Keywords: Condensed Matter Physics; General Materials Science

Influence of proteins on the corrosion of a conventional and selective laser beam melted FeMn alloy in physiological electrolytes - Huang, Jingyuan; Gonzalez Orive, Alejandro; Krüger, Jan Tobias; Hoyer, Kay-Peter; Keller, Adrian; Grundmeier, Guido (Corrosion Science)
Keywords: General Materials Science; General Chemical Engineering; General Chemistry

Modification of Iron with Degradable Silver Phases Processed via Laser Beam Melting for Implants with Adapted Degradation Rate - Krüger, Jan Tobias; Hoyer, Kay-Peter; Andreiev, Anatolii; Schaper, Mirko; Zinn, Carolin (Advanced Engineering Materials)
Keywords: Condensed Matter Physics; General Materials Science